Effect of high-tone external muscle stimulation on fatigue and functional outcomes in multiple sclerosis: A randomized controlled trial - Yassin Turky, Khalid Taha; Shalaby, Nevin M; Abdelmonem, Asmaa Foad; Abdeldayem, Tayseer Saber; Mohammed Sarhan , Mohammed Ali; M Omar , Ghada S; El-Din Mahmoud, Lama Saad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
A major symptom experienced by subjects with multiple sclerosis is fatigue, which induces a decline in physical, cognitive, and functional capacity. Exercise and electrotherapy are cornerstones of rehabilitation that elicit acceptable effects on feelings of fatigue and on performing activities of daily living. A randomized controlled trial was conducted to investigate the effects of high-tone external muscle stimulation on fatigue and functional outcomes in multiple sclerosis patients. A total of 40 multiple sclerosis patients were allocated randomly to either: the study or control groups. The study group received high-tone external muscle stimulation, while the control group received a conventional selected exercise training program. Both groups received 3 sessions per week for one month. Both groups showed a significant improvement post-study compared with pre-study. There was a significant reduction in Disability Status Scale (p=0.002), Fatigue Severity Scale scores (p=0.004), and total scores of Modified Fatigue Impact Scale (p=0.001) of the study group compared with that of the control group. High-tone external muscle stimulation showed an important improvement effect for both fatigue and functional outcomes in multiple sclerosis patients, being more effective than the conventional exercise training program; therefore, it should be considered a beneficial treatment method for patients with multiple sclerosis.